2007
DOI: 10.1007/s11064-007-9472-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Ethanol Consumption on Brain Synaptosomes and Protective Role of Betaine

Abstract: To evaluate the cytotoxic effects of chronic ethanol consumption on brain cerebral synaptosomes and preventive role of betaine as a methyl donor and S-adenosylmethionine precursor, 24 male Wistar rats were divided into three groups: control, ethanol (8 g/kg/day) and ethanol plus betaine(0.5% w/v) group. Animals were fed 60 ml/diet per day for two months, then sacrificed. Malondialdehyde (MDA), protein carbonyl contents and adenosine deaminase (ADA) activities were determined in synaptosomal/mitochondrial enric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 41 publications
3
12
0
Order By: Relevance
“…The unpaired electron present in the hydroxyl free radical, which is mainly responsible for the restraint stress-induced oxidative damage to the lymphoid tissues might have been trapped and subsequently dismuted by betaine. Earlier reports (Pourahmad et al 2005;Kanbak et al 2008) indicated that betaine had a potent reducing effect on the production free radicals in rats exposed to cytotoxicity. The protective effect of betaine against restraint stress-induced oxidative stress observed in this study may also be associated with the restoration of SAM, which contributes to an increase in the supply of substrate needed for the synthesis of GSH that protects the cell from reactive metabolites and reactive oxygen species.…”
Section: Resultsmentioning
confidence: 95%
“…The unpaired electron present in the hydroxyl free radical, which is mainly responsible for the restraint stress-induced oxidative damage to the lymphoid tissues might have been trapped and subsequently dismuted by betaine. Earlier reports (Pourahmad et al 2005;Kanbak et al 2008) indicated that betaine had a potent reducing effect on the production free radicals in rats exposed to cytotoxicity. The protective effect of betaine against restraint stress-induced oxidative stress observed in this study may also be associated with the restoration of SAM, which contributes to an increase in the supply of substrate needed for the synthesis of GSH that protects the cell from reactive metabolites and reactive oxygen species.…”
Section: Resultsmentioning
confidence: 95%
“…Chronic and excessive ethanol consumption is associated with various biochemical and physiological changes in the central nervous system (CNS). The most affected brain regions seem to be superior frontal association complex, hypothalamus, and cerebellum [35].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, brain tissues have unique characteristics that make them especially susceptible to damage due to low levels of antioxidant defenses [10]. Lipid peroxidation is one of the consequences of oxidative stress induced by metabolism of ethanol [35]. In this regard, a previous study demonstrated that chronic gestational exposure to alcohol caused a decrease in the membrane integrity while increasing oxidative stress in cerebellar neurons [48].…”
Section: Introductionmentioning
confidence: 99%
“…Betaine, also being a molecular chaperone, protects the cells against oxidative stress and mitohondrial damage. In another study, it was shown that betaine might protect lysosomal membranes with a 30-day pretreatment study [29]. Kim et al found that betaine supplementation is protective against necrotic damage [30].…”
Section: Discussionmentioning
confidence: 98%